2021
DOI: 10.3389/fmed.2021.724319
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Organ Failure Assessment Score for Prediction of Mortality of Patients With Rhabdomyolysis Following Exertional Heatstroke: A Longitudinal Cohort Study in Southern China

Abstract: Background: Heatstroke is a medical emergency that causes multi-organ injury and death without intervention, but limited data are available on the illness scores in predicting the outcomes of exertional heat stroke (EHS) with rhabdomyolysis (RM). The aim of our study was to investigate the Sequential Organ Failure Assessment (SOFA) score in predicting mortality of patients with RM after EHS.Methods: A retrospective cohort study was performed, which included all patients with EHS admitted into the intensive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“… 29 Recent studies have reported that the content of the CK and MB levels were powerfully elevated in the nonsurvival group of EHS patients within 24 h in ICU, which indicated that RM has an important contribution to the mortality of EHS patients. 30 , 31 Fer‐1 was identified as a small molecule inhibitor of ferroptosis. 11 In the current study, the treatment of Fer‐1 significantly attenuated the skeletal muscle injury in RM following EHS compared with other forms of cell death inhibitors, which is manifested by diminishing the increased serum CK and MB levels induced by EHS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 Recent studies have reported that the content of the CK and MB levels were powerfully elevated in the nonsurvival group of EHS patients within 24 h in ICU, which indicated that RM has an important contribution to the mortality of EHS patients. 30 , 31 Fer‐1 was identified as a small molecule inhibitor of ferroptosis. 11 In the current study, the treatment of Fer‐1 significantly attenuated the skeletal muscle injury in RM following EHS compared with other forms of cell death inhibitors, which is manifested by diminishing the increased serum CK and MB levels induced by EHS.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the standard mortality ratio, a key element in intensive care unit (ICU), is calculated based on the data available within the first 24 h of ICU stay 29 . Recent studies have reported that the content of the CK and MB levels were powerfully elevated in the nonsurvival group of EHS patients within 24 h in ICU, which indicated that RM has an important contribution to the mortality of EHS patients 30,31 . Fer‐1 was identified as a small molecule inhibitor of ferroptosis 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have revealed the potential usefulness of the SOFA score 3 7 , 9 , 10 . Here, we have also shown an advantage of using SOFA score for predicting the outcome of patients included in the heatstroke database.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, the Sequential Organ Failure Assessment (SOFA) score is widely used to assess multiple organ dysfunction or failure as the main causes of death in critically ill patients 8 . Prior studies have suggested that the SOFA score is also useful for predicting mortality in patients with heatstroke 3 7 , 9 , 10 . However, those studies exhibited some weaknesses, including the use of populations comprising only exertional heatstroke, and single-center designs.…”
Section: Introductionmentioning
confidence: 99%
“…ALI was also found in mouse and rat models of heatstroke (21,99,158,(177)(178)(179)(180)(181)(182)(183). Rhabdomyolysis is more common in patients with EHS, and several possible mechanisms cause such phenomenon (3,166,(184)(185)(186)(187)(188)(189)(190)(191)(192)(193). One potential mechanism is the elevated muscle tension caused by strenuous activity, which increases the chance of tissue injury (184).…”
Section: Tissue Injury Responsesmentioning
confidence: 99%